Analisis Pengaruh Brand Resonance, Brand Characteristic dan Brand Trust terhadap Brand Loyalty pada Produk Scarlett Whitening di Surakarta - Fadli, Mohammad Khoirul; Nasir, Moechammad (IAI Nasional Laa Roiba Bogor, 2024)
The objective of this studies is to examine and discusing the impact of brand resonance, brand characteristics and brand trust on brand loyalty in Scarlett Whitening products in Surakarta. Problem statement in this studies revolves around whether brand resonance, brand characteristics and exert a substantial influence on brand loyalty. Conducted as a survey with a quantitativ approach, the primari data were collected through questionn distributed via Google Form. The respondents sampled for this research are individuals who use Scarlett Whitening products in Surakarta. The entire consumer population using Scarlett Whitening products in Surakarta is considered the scope of this study, and the sampling technique employed is non-probability sampling through purposive sampling, with a total of 200 respondents. The hypotheses put forward posit that brand resonance is expected to significantly impact brand loyalty (H1), brand characteristics are anticipated have significant effect on brand loyalty (H2) and brand trust are anticipated have significant effect on brand loyalty(H3). The research findings indicate that both brand resonance, brand characteristics and brand trust indeed have a significant influence on brand loyalty. In conclusion, this study establishes that brand resonance (X1), brand characteristics (X2) and brand trust (X3) significantly contribute to brand loyalty (Y) for Scarlett Whitening products in Surakarta.